Anoctamin 5 mutation leads to abnormal bone homeostasis of GDD by regulating AMPK-dependent glucose metabolism - Li, Hongyu; Xu, Huichong; Sun, Kaiwen; Wang, Shengnan; Zhang, Mingyue; Lin, Liqi; Zhang, Shuai; Dong, Rui; Hu, Ying (Frontiers in Endocrinology, 2026)
IntroductionGnathodiaphyseal Dysplasia (GDD) characterized by enhanced bone mass and spontaneous fractures is a rare autosomal dominant genetic disease caused by Anoctamin 5 (ANO5) mutations. Deletion or mutation in ANO5 exhibited abnormal bone metabolism of GDD manifested by increased osteogenesis and reduced osteoclastogenesis. However, the mechanism is not fully understood.MethodsAno5Cys360Tyr knock-in mouse model was used. Mouse calvarial osteoblast (mCOB) and bone marrow macrophage (BMM) from homozygous knock-in (Ano5KI/KI) and wildtype mice were cultured in vitro. Compound C was selected to inhibit AMPK activity.ResultsWe found that Ano5Cys360Tyr mutation accelerated glycolysis and PGC1a-dependent mitochondrial respiration of osteoblast. Abnormal mitochondrial structure and function caused by PGC1b downregulation was observed in Ano5KI/KI osteoclast. Furthermore, ANO5 mutation promoted the phosphorylation of AMPK, the classical sensor of energy metabolism. Inhibiting AMPK reduced glycolysis in osteoblast and maintained the mitochondrial homeostasis between osteoblast and osteoclast by suppressing PGC1a and promoting PGC1b respectively, to restrain bone formation and restore osteoclastogenesis. AMPK inhibitor reversed the bone phenotype of GDD by restraining bone formation and restoring osteoclastogenesis.DiscussionWe highlighted the critical role of glucose metabolic distemperedness mediated by AMPK activation in GDD, which developing a potential therapeutic strategy targeted for treatment of GDD.